The trouble with community : anthropological reflections on movement, identity and collectivity - Amit, Vered, 1955- (Anthropology, culture, and society., 2002)
The authors reappraise the concept and the reality of 'community', in the light of globalization, religious fundamentalism, identity politics, and renascent localisms.